The Sequence-specific Peptide-binding Activity of the Protein Sulfide Isomerase AGR2 Directs Its Stable Binding to the Oncogenic Receptor EpCAM - Mohtar, M Aiman; Hernychova, Lenka; O'Neill, J Robert; Lawrence, Melanie L; Murray, Euan; Vojtesek, Borek; Hupp, Ted R (Molecular & cellular proteomics, 2018)
AGR2 is an oncogenic endoplasmic reticulum (ER)-resident protein disulfide isomerase. AGR2 protein has a relatively unique property for a chaperone in that it can bind sequence-specifically to a specific peptide motif (TTIYY). A synthetic TTIYY-containing peptide column was used to affinity-purify AGR2 from crude lysates highlighting peptide selectivity in complex mixtures. Hydrogen-deuterium exchange mass spectrometry localized the dominant region in AGR2 that interacts with the TTIYY peptide to within a structural loop from amino acids 131-135 (VDPSL). A peptide binding site consensus of Tx[IL][YF][YF] was developed for AGR2 by measuring its activity against a mutant peptide library. Screening the human proteome for proteins harboring this motif revealed an enrichment in transmembrane proteins and we focused on validating EpCAM as a potential AGR2-interacting protein. AGR2 and EpCAM proteins formed a dose-dependent protein-protein interaction in vitro Proximity ligation assays demonstrated that endogenous AGR2 and EpCAM protein associate in cells. Introducing a single alanine mutation in EpCAM at Tyr251 attenuated its binding to AGR2 in vitro and in cells. Hydrogen-deuterium exchange mass spectrometry was used to identify a stable binding site for AGR2 on EpCAM, adjacent to the TLIYY motif and surrounding EpCAM's detergent binding site. These data define a dominant site on AGR2 that mediates its specific peptide-binding function. EpCAM forms a model client protein for AGR2 to study how an ER-resident chaperone can dock specifically to a peptide motif and regulate the trafficking a protein destined for the secretory pathway.
Keywords: Protein Binding; Recombinant Proteins; proteiny; protoonkogenní proteiny c-mdm2; Oncogene Proteins; Epithelial Cell Adhesion Molecule; Proto-Oncogene Proteins c-mdm2; MFC-7 buňky; MCF-7 Cells; rekombinantní proteiny; vazba proteinů; mukoproteiny; lidé; adhezní molekula epiteliálních buněk; onkogenní proteiny; Humans; Peptides; peptidy; Proteins; Mucoproteins